Cardiovascular outcomes after cardiac resynchronization therapy in cardiac amyloidosis. (3rd November 2021) - Fischer, Kilian; Lellouche, Nicolas; Damy, Thibaud; Martins, Raphaël; Clementy, Nicolas; Bisson, Arnaud; Lesaffre, François; Espinosa, Madeline; Garcia, Rodrigue; Degand, Bruno; Serzian, Guillaume; Jourda, François; et al.
Abstract: Aims: Cardiac resynchronization therapy (CRT) is highly effective in dilated cardiomyopathy (DCM) patients with impaired left ventricular ejection fraction (LVEF) and left bundle block branch. In cardiac amyloidosis (CA) patients, left ventricular dysfunction and conduction defects are common, but the potential of CRT to improve cardiac remodelling and survival in this particular setting remains undefined. We investigated cardiovascular outcomes in CA patients after CRT implantation in terms of CRT echocardiographic response and major cardiovascular events (MACEs). Methods and results: Our retrospective study included 47 CA patients implanted with CRT devices from January 2012 to February 2020, in nine French university hospitals (77 ± 6 years old, baseline LVEF 30 ± 8%) compared with propensity‐matched (1:1 for age, LVEF at implantation, and CRT indication) DCM patients with a CRT device. CA patients had lower rates of CRT response (absolute delta LVEF ≥ 10%) compared with DCM patients (36% vs. 70%, P = 0.002). After multivariate Cox analysis, CA was independently associated with MACE (hospitalization for heart failure/cardiovascular death) [hazard ratio (HR) 3.73, 95% confidence interval (CI) 1.85–7.54, P < 0.001], along with the absence of CRT response (HR 3.01, 95% CI 1.56–5.79, P = 0.001). The presence of echocardiographic CRT response (absolute delta LVEF ≥ 10%) was the only predictive factor of MACE‐free survival in CA patients (HR 0.36, 95% CI 0.15–0.86, P = 0.002). Conclusion: Compared with a matched cohort of DCM patients, CA patients had a lower rate of CRT response and consequently a worse cardiovascular prognosis after CRT implantation. However, CRT could be beneficial even in CA patients given that CRT response was associated with better cardiac outcomes in this population.